Genetic Associations Between IL-6 and the Development of Autoimmune Arthritis Are Gender-Specific - Hong, Jianqiao; Qu, Zihao; Ji, Xiaoxiao; Li, Congsun; Zhang, Geng; Jin, Ciliang; Wang, Jie; Zhang, Yongxing; Shen, Yue; Meng, Jiahong; Zhou, Chenhe; Fang, Chaohua; et al. (Frontiers in Immunology, 2021)
Objectives To find out the genetic association between IL6 and autoimmune arthritis. Methods We performed a two‐sample Mendelian randomization (MR) study, using multiple genome-wide association studies (GWAS) datasets. Further, a sex-stratified MR study was performed to identified sexual dimorphism in the association between IL6 and autoimmune arthritis. Then, LocusZoom plots were displayed based on the IL6R gene region to present evidence of genetic colocalization between diseases. Results The MR result denoted a genetic association between increased level of IL-6 signaling and risk of RA (β=0.325, 95%CI 0.088, 0.561, p=7.08E-03) and AS (β=1.240, 95%CI 0.495, 1.980, p=1.1E-03). Accordingly, sIL6R was found negatively correlation with onset of RA (β=-0.020, 95%CI -0.0320, -0.008, p=1.18E-03) and AS (β=-0.125, 95%CI -0.177, -0.073, p=2.29E-06). However, no genetic association between IL6/sIL6R and PsA was detected. The gender-stratified MR analysis showed that IL6 was associated with AS in male population, with RA in female population and with PsA in male population. Additionally, ADAR, a gene identified by the sensitive test, could be the reason for non-significant association between IL6 and PsA in pooled population. Conclusion Our findings showed that overactive IL6 signal pathway led to autoimmune arthritis, especially in RA and AS. The Sexual differences was also observed in IL6-intermediate susceptibility to autoimmune arthritis.